The resource base of the Andean civilizations - Morris, Arthur (Pontificia Universidad Católica del Perú. Fondo Editorial, 1997)
The understanding of the prehistoric Andean cultures has shifted noticeably in recent decades, attributing to them higher levels of achievement, both in qualitative and quantitative terms. One of the central elements in the re-evaluation is the realization that a strong economic base, including agricultural production, was in existence from at least 2000 years before the present. This paper brings together some of the newer evidence, to show that the local base was even stronger than is currently acknowledged by scientists working in disparate specialisms. We focus on the pre-Inca, Tiwanaku state which centred on the Lake Titicaca basin.
Keywords: Cultura Tiahuanaco; https://purl.org/pe-repo/ocde/ford#5.07.00